Contact Angle Measurement for The Surface Characterization of Solids - Subedi, D. P. (Himalayan Physics, 2011)
This paper reports a description of the theory of contact angle measurement and its use for the determination of surface energy of solids. The main objective of the work is to present a convenient approach to explain wetting phenomenon using contact angle theory. A brief review of Young’s equation and Young- Dupre equation is also presented followed by an extended Fowke’s equation widely used for the calculation of surface energy of solids. The two liquid model has been applied to determine the surface energy of polycarbonate and low density polyethylene. Key words: Contact angle; Surface energy; Surface characterization; Wettability; Young’s equation; Fowke’s model The Himalayan Physics Vol.2, No.2, May, 2011 Page:1-4 Uploaded Date: 31 July, 2011